(untitled) (Revista Espinhaço, 2025)
In 2023, the Food Acquisition Program (PAA) marked its second decade of existence. The program has become the second main instrument for the productive inclusion of family farmers in Brazil, aiming at building markets focused on food and nutritional security for the most vulnerable population. Since its inception and across different government administrations, Brazil managed to exit the World Hunger Map in 2014, but re-entered it in 2022. Despite this setback, the program has gradually expanded the productive chain of family farming and benefited from legislation that generated practical effects for its improvement and for meeting the demands of both producers and consumers. Academic literature highlights several achievements promoted by the program, such as guaranteed commercialization and sales; income growth; improved quality of life and greater autonomy for producers; diversification of production; productive insertion; and the expansion of the social assistance network receiving the products; among others.